Bone mineral density and its correlation with clinical and laboratory factors in chronic peritoneal dialysis patients - (:unkn) unknown (SPRINGER JAPAN KK, 2006)
The aim of this study was to assess the clinical and laboratory correlations of bone mineral density (BMD) measurements among a large population of patients on chronic peritoneal dialysis (PD). This cross-sectional, multicenter study was carried out in 292 PD patients with a mean age of 56 +/- 16 years and mean duration of PD 3.1 +/- 2.1 years. Altogether, 129 female and 163 male patients from 24 centers in Canada, Greece, and Turkey were included in the study. BMD findings, obtained by dual-energy X-ray absorptiometry (DEXA) and some other major clinical and laboratory indices of bone mineral deposition as well as uremic osteodystrophy were investigated. In the 292 patients included in the study, the mean lumbar spine T-score was -1.04 +/- 1.68, the lumbar spine Z-score was -0.31 +/- 1.68, the femoral neck T-score was -1.38 +/- 1.39, and the femoral neck Z score was -0.66 +/- 1.23. According to the WHO criteria based on lumbar spine T-scores, 19.2% of 292 patients were osteoporotic, 36.3% had osteopenia, and 44.4% had lumbar spine T-scores within the normal range. In the femoral neck area, the prevalence of osteoporosis was slightly higher (26%). The prevalence of osteoporosis was 23.3% in female patients and 16.6% in male patients with no statistically significant difference between the sexes. Agreements of lumbar spine and femoral neck T-scores for the diagnosis of osteoporosis were 66.7% and 27.3% and 83.3% for osteopenia and normal BMD values, respectively. Among the clinical and laboratory parameters we investigated in this study, the body mass index (BMI) (P < 0.001), daily urine output, and urea clearance time x dialysis time/volume (Kt/V) (P < 0.05) were statistically significantly positive and Ca x PO4 had a negative correlation (P < 0.05) with the lumbar spine T scores. Femoral neck T scores were also positively correlated with BMI, daily urine output, and KT/V; and they were negatively correlated with age. Intact parathyroid hormone levels did not correlate with any of the BMD parameters. Femoral neck Z scores were correlated with BMI (P < 0.001), and ionized calcium (P < 0.05) positively and negatively with age, total alkaline phosphatase (P < 0.05), and Ca x P (P < 0.01). The overall prevalence of fractures since the initiation of PD was 10%. Our results indicated that, considering their DEXA-based BMD values, 55% of chronic PD patients have subnormal bone mass-19% within the osteoporotic range and 36% within the osteopenic range. Our findings also indicate that low body weight is the most important risk factor for osteoporosis in chronic PD patients. An insufficient dialysis dose (expressed as KT/V) and older age may also be important risk factors for osteoporosis of PD patients.
Keywords: bone mineral density; dual-energy X-ray absorptiometry (DEXA); peritoneal dialysis; body weight; RISK-FACTORS; FRACTURES; DENSITOMETRY